2013
DOI: 10.17503/agrivita-2013-35-1-p081-087
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Phosphate Fertilization Method in Wetland Rice

Abstract: The research aimed to assess better P fertilization method for wetland rice which used quickly dissolving P fertilizer given in split application. The research concluded that the application of quickly dissolving P fertilizer to Alfisol and Oxisol applied in split application twice (0 and 30 days after planting) and three times (0, 15 and 30 days after planting) increased the eficiency of P fertilization in wetland rice. The split application of 75 kg ha -1 (50% of recommended dose) in Alfisol yielded dry seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These results are in line with previous research. Cahyono & Hartati (2013) reported the effect of FDP fertilizer use on lowland rice plants. The application of 75 kg/ha FDP fertilizer (a half-recommended dose) produced rice grains as high as 7.360 kg/ha when applied in 3 times split application.…”
Section: P Uptake Efficiency On the Application Of Fdp Fertilizermentioning
confidence: 99%
“…These results are in line with previous research. Cahyono & Hartati (2013) reported the effect of FDP fertilizer use on lowland rice plants. The application of 75 kg/ha FDP fertilizer (a half-recommended dose) produced rice grains as high as 7.360 kg/ha when applied in 3 times split application.…”
Section: P Uptake Efficiency On the Application Of Fdp Fertilizermentioning
confidence: 99%
“…Knowledge of how rice responds to the P fertilizer application time during the growing season is essential for the development of efficient P fertilizer recommendations (Slaton et al, 2002). Cahyono and Hartati (2013) reported that improving the efficiency of P fertilizer can be reached by providing a quickly dissolving phosphate fertilizer. However, as phosphate forms a reaction with other compounds soon after release from the fertilizer, a proper method of P application, split application, should be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Kartika et al (2018) reported that planting pattern and split N fertilizer application increased leaf chlorophyll and nitrogen content during vegetative stage and yield in rice cultivated at riparian wetlands. Increase in rice yield was also reported by Cahyono & Hartati (2013) if P fertlitizer was splitted into two or three times of application. Marlina, Gofar, Subakti, & Rahim (2014) found that composition of 75% of recommended inorganic fertilizer rate with additional biofertilizer increased productive tillers, number of grains per panicle, and weight of milled dry rice.…”
Section: Affordable Technologies and Their Impactsmentioning
confidence: 56%